Physiology and Morphological Correlates of Excitatory Transmission are Preserved in Glutamine Transporter SN1-Depleted Mouse Frontal Cortex. (15th October 2020) - Popek, M.; Bobula, B.; Sowa, J.; Hess, G.; Frontczak-Baniewicz, M.; Albrecht, J.; Zielińska, M.
Highlights: Excitatory transmission is preserved in glutamine transporter SN1 depleted mouse frontal cortex. SN1 transporter loss resulted in a centrally located unaltered number of synaptic vesicles. SN1 transporter depletion resulted in the unchanged length of the active zone in synapses. Synaptic proteins synaptophysin, synaptotagmin, and vit1A weren't affected by SN1 decrease. Abstract: Glutamine is an astroglia-derived precursor of the neurotransmitter glutamate, and its astroglia-to-neuron transfer is controlled by distinct glutamine transporters on the astrocytic and neuronal sites. In this study, we focused on the role of astrocytic glutamine efflux-mediating system N transporter SN1 in the maintenance of glutamatergic neurotransmission by analyzing the electrophysiological parameters ex vivo in the brain slices from control mice and mice in which vivo-morpholino technique was used to diminish SN1 protein. The glutamatergic transmission was characterized by electrophysiological recordings, ultrastructure of neuron terminals, and determination of proteins related to glutamate synaptic transmission: synaptophysin, synaptotagmin, and vit1A. The space-restricted ∼51, 5% reduction of SN1 protein did not affect the expression of the neuronal glutamine transporter SAT2. SN1 depletion resulted in a reduction of field potentials (FPs), unaltered frequency of spontaneous and miniature excitatory postsynaptic currents (sEPSCs/mEPSCs), and presented a tendency towards a decrease of long-term potentiation (LTP). Ultrastructurally, preserved number of synaptic vesicles, primarily localized centrally of the cell body, correlates with unchanged levels of synaptic proteins. Collectively, the study indicates that glutamatergic transmission proceeds relatively independently of the SN1 - mediated glutamine transfer to the synapse.